Environmental risk assessment study Mak-Ban Geothermal Complex - Echavez, Julia W.
Recent government regulations on environmentally critical projects including energy projects require the submittal of Environmental Risk Assessment (ERA) reports. Unlike in the Environmental Impact Statement reports, the Department of Environment and Natural Resources (DENR however did not provide for guidelines on the format or contents of ERA reports. This is probably because ERA might be considered as a relatively new discipline in the Philippine setting. Because of the significance of the geothermal electric contribution to the Philippine energy, the author set to present a methodology on environmental risk assessment (ERA) for geothermal power projects. THe study framework consists of five components: hazard identification; hazard accounting; environmental pathway evaluation; risk characterization; and risk management. These were lumped into: hazards assessment, risk assessment, and risk management.